How artificial potential field algorithms can help to simulate trade-offs in movement behaviour of reef fishes - Kruse, Maren; Meyer, Christian; Schneekloth, Fabian; Reuter, Hauke (Frontiers in Marine Science, 2022)
Space use patterns in reef fish result from the interactions between individual movement behaviour and characteristics of the environment. Herbivorous parrotfishes, for instance, are constrained by the availability of resources and different predation risks. The resulting spatial distribution of the fish population can strongly influence community composition and ecosystem resilience. In a novel approach, we combine individual-based modelling (IBM) with potential fields (i.e., representation of the environment as grid cells of repellent and attracting forces), to realistically represent fish movements and the decision-making process. The coupling of individual fish bioenergetics with a navigation capacity provides a mechanistic basis to analyze how the habitat structure influences population dynamics and space utilization. Model results indicate that movement patterns and the resulting spatial distributions strongly depend on habitat fragmentation with reproduction being a particularly susceptible process on the individual level. The resulting spatial distributions of the population are more irregularly distributed among coral reef patches the more the coral reef habitat becomes fragmented and reduced. This heterogeneity can have strong implications for the delivered ecosystem functioning, e.g., by concentrating or diluting the grazing effort. Our results also highlight the importance of incorporating individual foraging-path patterns and the spatial exploitation of micro-habitats into marine spatial planning: The integration of potential fields into IBMs proves a promising strategy to advance our understanding of complex decision-making in animals by implementing a more realistic and dynamic decision-making process, in which each fish weighs different rewards and risks of the environment. This information may help to identify core areas and essential habitat patches and assist in effective marine spatial planning .